Dimensional synthesis of six-bar Stephenson III mechanism for 12 precision points path generation. (2016) - Nafees, Khalid; Mohammad, Aas
The technological advancements require sophisticated manufacturing procedures wherein requirement to design mechanisms that can precisely follow a specified path through a given number of precision points are to be fulfilled. With these objectives, a six-bar Stephenson III linkage mechanism, having one degree of freedom has been dimensionally synthesised for 12 precision points. The complex number dyadic and triadic loop closure equations have been used to synthesise the mechanism for path generation. In this approach, loop closure equations are solved simultaneously for 12 displacement positions of coupler tracing point and 12 orientation positions of various links for which the output link oscillates. The prescribed parameters are displacement vector (δj) and coupler link motion and the designer is not constrained to restrict the remaining orientation angles of links. Finally, a code has been developed in MATLAB to solve these loop closure equations for determination of the dimensional length of each link.